Characterization Of Steel Slag For Incorporation Into Red Ceramics - Sergio Neves Monteiro (The Minerals, Metals and Materials Society, 2006)
This work had as its objective the characterization of a waste material, steel slag, generated from an integrated steel plant, with a view to its recycling and incorporation into red ceramics fabrication. The characterization was performed in terms of chemical composition by X-ray fluorescence (XRF), particles size distribution, X-ray diffraction (XRD), thermal analysis (DTA/TG) and scanning electron microscopy (SEM). The results indicate that the steel slag presents high amount of Ca, Fe, Mg and Si. The weight loss of the steel slag at temperatures above 800oC is associated with calcium carbonate decomposition. The coarse particle size of the steel slag is inadequate for its direct recycling into red ceramic fabrication. It is necessary to screen or to grind the waste. As a possible solution, it is suggested that screening or grinding the steel slag to a convenient particle size distribution would allow its successful industrial incorporation into red ceramics products.